Russian Experience of Transport Extracorporeal Membrane Oxygenation - D. A. Shelukhin; A. V. Karpov; M. V. Ketskalo; K. K. Gubarev (Неотложная медицинская помощь, 2021)
Relevance. The present time can be called a period of accumulation of experience of national health systems in different countries of the world in the application of transport extracorporeal membrane oxygenation (ECMO) technology at the pre- and inter-hospital stages of evacuation of patients to specialized ECMO-therapy centers. The role of such centers is to provide timely advice and, if necessary, perform inter-hospital evacuation.Material and methods. The study summarized and analyzed with the help of the national register “RosECMO” the own experience of 13 hospitals in the Russian Federation, who performed 68 inter-hospital evacuations under ECMO conditions by different modes of transport in patients of different age groups with symptoms of circulatory and respiratory failure. The following parameters were evaluated: characteristics of transport ECMO, clinical manifestations of potentially negative effects of transport, hospital survival, as well as the effect of experience (less and more than 10 cases of transport ECMO) of the presented clinics on the difference in the results obtained.Results. Connecting patients to the ECMO device reduces the likelihood of death on the SOFA and APACHE IV scales by 1.2 times (p <0.0001) and 1.4 times (p<0.0001), respectively. Despite the absence of deaths during inter-hospital transportation of patients under ECMO conditions, 14.93% of patients died within 3 days from the moment of their execution, without a significant difference in clinics with different practical experience. The overall hospital survival rate of ECMO transport scenarios in all 13 clinics of the Russian Federation was comparable to the data of the international register 48.52% versus 48.81%, at the same time it was significantly lower (1.3 times) in the group of clinics with less clinical experience 40% versus 52.08% (p<0.0001).Conclusion. The results of the first stage of the study we obtained indicate the prospects of using the method of extracorporeal membrane oxygenation at the stage of inter-hospital evacuation, due to the effective stabilization of the patient’s condition and a significant reduction in the risks of the likelihood of death. Clinics with less clinical experience showed significantly worse results of hospital survival of patients who underwent inter-hospital transportation under conditions of extracorporeal membrane oxygenation compared to clinics with more clinical experience, which can be a significant argument in adopting a model for the development of specialized regional centers for extracorporeal membrane oxygenation. The experience accumulated over the past six years and the analysis of new data from the register of transport cases of extracorporeal membrane oxygenation of the national healthcare system will make it possible to formulate the correct trajectory for the development of the method of extracorporeal membrane oxygenation and its application, including at the stage of pre- and inter-hospital evacuations of patients.